2011
DOI: 10.1176/ps.62.8.pss6208_0893
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Investigation of Self-Stigma Among Adolescents Taking Psychiatric Medication

Abstract: The adolescent model was similar to yet distinct from the adult model, and developmental differences may contribute to the variation. The need for future research to validate an adolescent self-stigma model is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…Another example reveals the connection between understanding and accepting: "he knows that like I understand him and why he does the things he does, like and I accept him for who he is" (KH: Family). The battle for acceptance of self is common among young people with mental illnesses (Kranke, Floersch, Kranke, & Munson, 2011), and having a relationship with someone who provides a feeling of acceptance and unconditional positive regard can be critical to healing.…”
Section: Characteristics Of Supportive Relationships and Nature Of Sumentioning
confidence: 99%
“…Another example reveals the connection between understanding and accepting: "he knows that like I understand him and why he does the things he does, like and I accept him for who he is" (KH: Family). The battle for acceptance of self is common among young people with mental illnesses (Kranke, Floersch, Kranke, & Munson, 2011), and having a relationship with someone who provides a feeling of acceptance and unconditional positive regard can be critical to healing.…”
Section: Characteristics Of Supportive Relationships and Nature Of Sumentioning
confidence: 99%
“…The conceptual adolescent self-stigma model (Kranke et al, 2011) has three potential components: 'stereotype,' 'differentiate,' and 'protect.' Adolescents respond to their illness or use of medications by linking their personal meanings/interpretations to stereotypes.…”
Section: Adolescent Self-stigma Modelmentioning
confidence: 99%
“…As the extant literature (Hinshaw, 2007;Karp, 2006;Kranke et al, 2010, Kranke et al, 2011 indicates, adolescent and adult experience of stigma are shaped by developmental tasks. For instance, adults are consumed with issues related to career, intimacy, and secondary education (Wahl, 1999).…”
Section: Contextual Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although youth coped with stigma similarly to adults (i.e., secrecy, shame, and limiting interaction), the data suggests that adolescents experienced different limited opportunities than adults, particularly those associated with social interaction and peer acceptance, which are common developmental work of adolescents. In addition, a study of self-stigma among adolescents indicated that their self-stigma process differed from the adult process (Kranke, Floersch, Kranke, & Munson, 2011). In particular, statements from African American adolescents revealed more negative stereotypes of people with mental illness and that many of these stereotypes were intensified by important relational figures, such as parents.…”
Section: Stigmamentioning
confidence: 99%